Putting into Practice Gap Tasks in an ESP Classroom forMedicine Personnel at Universidad de Costa Rica = poniendo en práctica actividades que requieren de la interacción verbal paracompletar la información faltante en una clase de inglés con fines específicos impartidapara el personal de medicina de la Universidad de Costa Rica - Villanea Morales, Marta Lucía 1962-
This paper presents the results of a study conducted in a group of eight students in an ESP course taught by Practicum students at the School of Medicine at the University of Costa Rica. The results indicate that the student-teachers based their lessons mostly on information gap tasks. Besides, this study revealed that the activities presented followed a common pattern avoiding variety. In addition, the study reflected that the activities used during the days of observation, did not fulfilled the requirements of a good gap task in a hundred percent since the tasks did not promote spontaneous and creative communication. The correct use of gap tasks helps students to develop speaking skills in asafe and private environment.The outcomes of these kinds of tasks will always be positive as long as they are adequate, relevant, authentic, and achievable.